2020
DOI: 10.1039/c9tc05752h
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the photocatalytic activity of BiOX under solar light via selective crystal facet growth

Abstract: The selective crystal facet growth of BiOX (X = Cl, Br, I) is very significant since each facet possesses different physicochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 43 publications
5
25
0
Order By: Relevance
“…Tailoring of exposed facet should reduce the energy of high energy facet, where the use of a capping agent or structure directing agent is common bottom-up route. Although organic surfactants can perfectly accomplish this aim, most of them are difficult to be completely removed from the catalyst surface, which is a hindrance to the reaction site. , By contrast, inorganic ions will be easily removed from the surface, but some cations with a lower valence state may enter the crystal, like Na + . Li et al have reported an excellent 18-faceted BiOCl flake with ternary facet cascade charge flow via a prolonged synthesis time strategy . However, this is a much more energy-intensive process.…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring of exposed facet should reduce the energy of high energy facet, where the use of a capping agent or structure directing agent is common bottom-up route. Although organic surfactants can perfectly accomplish this aim, most of them are difficult to be completely removed from the catalyst surface, which is a hindrance to the reaction site. , By contrast, inorganic ions will be easily removed from the surface, but some cations with a lower valence state may enter the crystal, like Na + . Li et al have reported an excellent 18-faceted BiOCl flake with ternary facet cascade charge flow via a prolonged synthesis time strategy . However, this is a much more energy-intensive process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the surface lattice oxygen atoms in the metallic oxide could directly take part in the oxidation process [12][13][14][15] . Compared with the broken of O-O bond in O2, O-metal bond could be easier to dissociate 4,[16][17][18][19][20] . Hence, it provides a possibility that surface lattice oxygen might be more beneficial for the occurrence of oxidation reaction compared with O2.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the bulk sample, catalysts with nanostructures generally exhibit increased photocatalytic activities because of the quantized sizes and, consequently, additional active sites. [ 184,185 ] As the bandgap decreases, the optimal light absorption range of the BiOX family gradually transforms from UV to the visible light region. Xiong et al.…”
Section: Pb‐free Ns2‐cation‐containing Semiconductors For Optoelectronic Applicationsmentioning
confidence: 99%